Pengaruh Promosi Penjualan H&M terhadap Keputusan Pembelian Konsumen: (Survei Pada Pengunjung Offline Store H&M) - Setia Amelia; Jamiati KN (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Sales promotion is important for every business in any field and industry. Because sales promotion has the benefit of increasing sales and also to introduce products from a brand. The sales promotion carried out by H&M is to create an Up to 50% End of Season Sale. This study aims to measure how much influence H&M Sales Promotion has on Consumer Purchasing Decisions. The main theory used in this study is which includes three dimensions, namely Consumer Promotion, Trade Promotion and Salesperson Promotion. The data collection technique used is Random Sampling. This research is indicated by the average value of respondents' answers to variable X of 4.42 where the value is classified as high (agree). and the average on variable Y of 4.32 which has a value classified as high (agree). the influence of H & M Sales Promotion on Consumer Purchasing Decisions can be seen from the (R) correlation of 0.785 which is fairly high and the R square value of 0.616 or 61.1% of the effect while the rest is influenced by other things.